Implementation of the Connected Mathematics Project Learning Model on Students' Mathematical Problem Solving Abilities - Harahap, Sinar Depi; Ahmad, Marzuki; Sabri, Sabri; Lubis, Ilham Sahdi (Jurnal Pendidikan MIPA, 2023)
Abstract: Low Mathematical Problem Solving Ability (MPSA) is a major problem in research. One learning model that supports increasing MPSA in learning is the Connected Mathematics Project (CMP) learning model. The aim of this research is to describe the implementation of the CMP learning model on students' MPSA. This type of research is quasi-experimental with a one group pretest posttest design. The research population was class VIII students' at MTsN 1 Padangsidimpuan consisting of 11 study groups. The research sample was students' from class VIII-11 with a total of 33 students'. The research instrument was the CMP learning management observation sheet and students' MPSA test. Analysis of data from observations was carried out descriptively and analysis of student MPSA data was carried out using inferential statistical tests using the paired t-test. The research results show that CMP learning management obtained an average score of 3.52 (good). Furthermore, analysis of the students' MPSA data shows a significance value of 0.00 which is smaller than the alpha level of 0.05 (there is a significant difference between the average pre-test and post-test scores). Furthermore, an n-gain value of 0.44 (Medium) was obtained. Thus it is concluded that the implementation of CMP learning on students' MPSA is effective. Keywords: implementation, CMP, problem solving, mathematics. Abstrak: Rendahnya Kemampuan Pemecahan Masalah Matematika (MPSA) merupakan masalah utama dalam penelitian. Salah satu model pembelajaran yang mendukung peningkatan MPSA dalam pembelajaran adalah model pembelajaran Connected Mathematics Project (CMP). Tujuan penelitian ini adalah untuk mendeskripsikan implementasi model pembelajaran CMP terhadap MPSA siswa. Jenis penelitian adalah quasi eksperimen dengan rancangan one group pretest posttest design. Populasi penelitian adalah siswa kelas VIII MTsN 1 Padangsidimpuan yang terdiri dari 11 Rombongan belajar. Sampel Penelitian adalah siswa kelas VIII-11 dengan jumlah siswa 33 orang. Instrumen penelitian adalah lembar observasi pengelolaan pembelajaran CMP dan Tes MPSA siswa. Analisis data hasil observasi dilakukan dengan deskriptif dan analisis data MPSA siswa dilakukan dengan uji statistik inferensial uji paired t-test. Hasil penelitian menunjukkan pengelolaan pembelajaran CMP memperoleh nilai rata rata 3,52 (baik). Selanjutnya analisi data MPSA siswa menunjukkan nilai signifikansi 0,00 lebih kecil dari taraf alpha 0,05 (terdapat perbedaan signifikan dari nilai rata rata pretes dan postes). Selanjutnya diperoleh nilai n-gain 0,44 (Sedang). Dengan demikian disimpulkan bahwa Implementasi pembelajaran CMP terhadap MPSA siswa adalah efektif.  Kata kunci: implementation, CMP, pemecahan masalah, matematika.DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp556-570